2017
DOI: 10.3389/fpsyg.2017.01045
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on the Attribution of Personality Traits to Bullies and Targets in a Workplace Setting

Abstract: Previous studies on the personality of bullies and targets have exclusively been based on self-report. Against this backdrop we conducted a between group experimental vignette study with three conditions, describing a bully, a target and a control, respectively. Students (n = 242) were recruited as participants and rated the target on the observer rating version of the NEO Five Factor Inventory-Revised reflecting the personality dimensions Neuroticism, Extroversion, Openness to experience, Agreeableness and Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 51 publications
2
16
0
3
Order By: Relevance
“…These distinct effects suggest that individuals have a more differentiated stereotype of an ostracizable face than merely that of a face that is perceived as either positive or negative. This ostracism stereotype is also in line with research that has demonstrated that the stereotypical image of a bully, a target that individuals may wish to ostracize, is that of a person low in agreeableness and conscientiousness (Pallesen, Nielsen, Mageroy, Andreassen, & Einarsen, 2017).…”
Section: Discussionsupporting
confidence: 83%
“…These distinct effects suggest that individuals have a more differentiated stereotype of an ostracizable face than merely that of a face that is perceived as either positive or negative. This ostracism stereotype is also in line with research that has demonstrated that the stereotypical image of a bully, a target that individuals may wish to ostracize, is that of a person low in agreeableness and conscientiousness (Pallesen, Nielsen, Mageroy, Andreassen, & Einarsen, 2017).…”
Section: Discussionsupporting
confidence: 83%
“…19,20 In a survey of adults, the experience of being victimized was shown to lead to high neuroticism. 21 Research on a 3-wave-survey with a long interval in a workplace showed that being victimized is associated with increased neuroticism, and neuroticism decreases in the absence of victimization. 22 These reports imply that being victimized increases neuroticism.…”
Section: Discussionmentioning
confidence: 99%
“…Rai and Agarwal (2019) examined personality as an antecedent of bullying and recommended to further investigate the phenomenon by arriving at a more authentic conclusion. These calls to explore personality traits of parties involved in bullying, associating personality traits with bullying, and establishing a cause-and-effect relationship between personality and workplace bullying for developing theoretical models (Zapf & Einarsen, 2003)and applied purposes (Nielsen et al, 2017;Pallesen, Nielsen, Magerøy, Andreassen, & Einarsen, 2017)necessitate further research in this avenue. As there is consistent cross-cultural validation of five-factor model of personality (McCrae& John, 1992), current study has used FFM of personality traits as suggested by Nielsen et al (2017).…”
Section: Introductionmentioning
confidence: 99%